1990
DOI: 10.1111/j.1349-7006.1990.tb02562.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Analysis of Tumor Vascularization in the Rat

Abstract: By using transparent chambers in rats, we have directly observed tumor‐induced neovascularization in the early stage and the formation of intricate networks in Yoshida rat ascites hepatoma AH109A and Sato lung carcinoma at high magnification. We counted branching point numbers per unit area in the microvascular network with and without tumors in order to clarify the sites from which new vascular sprouts originate. Branching point number per unit area in normal tissue was 13.6 ± 7.4/0.1 mm2 in the field near a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 18 publications
4
34
0
Order By: Relevance
“…Additionally, most tumor blood vessels have an irregular diameter and an abnormal branching pattern. For example, Hori and colleagues have shown that terminal arterioles in rat hepatoma or lung carcinomas approximated 50 branches per 0.1 mm 2 , as compared to 14 per 0.1 mm 2 in normal tissues (55). Interestingly, a similar phenomenon occurs in leukemia: irregular and complex branching of microvessels has been observed in leukemic bone marrow, compared with the single, straight microvessels without branching in normal bone marrow (56).…”
Section: Factors Impacting Tumor Distributionmentioning
confidence: 98%
“…Additionally, most tumor blood vessels have an irregular diameter and an abnormal branching pattern. For example, Hori and colleagues have shown that terminal arterioles in rat hepatoma or lung carcinomas approximated 50 branches per 0.1 mm 2 , as compared to 14 per 0.1 mm 2 in normal tissues (55). Interestingly, a similar phenomenon occurs in leukemia: irregular and complex branching of microvessels has been observed in leukemic bone marrow, compared with the single, straight microvessels without branching in normal bone marrow (56).…”
Section: Factors Impacting Tumor Distributionmentioning
confidence: 98%
“…For direct observation of changes in normal arterioles and tumour vessels caused by AC7700, transparent chambers (Hori et al, 1990) were implanted in dorsal skin flaps of rats under aseptic conditions. The chamber used in the present experiment was a 'sandwich' system (Yamaura and Sato, 1974) in which each chamber consists of a pair of identical titanium frames containing a circular quartz glass window 300 mm thick.…”
Section: Transparent Chamber Assaysmentioning
confidence: 99%
“…Rat transparent chambers (Hori et al, 1990) were implanted in dorsal skin flaps under aseptic conditions. Each chamber consisted of two identical titanium frames containing a circular quartz glass window 300 mm thick.…”
Section: Measurement Of Tbfmentioning
confidence: 99%